The influence of family socioeconomic status on college students’ mental health literacy: the chain mediating effect of parenting styles and interpersonal relationships - Wu, Jie; Shen, Haoyuan; Shen, Yunbo; Liao, Xianglin; Yu, Xianglian (Frontiers in Psychology, 2024)
With the increasing prevalence of mental health challenges among college students, understanding how family background and interpersonal dynamics affect mental health literacy is critical. This study examined the relationships between family socioeconomic status, mental health literacy, parenting styles, and interpersonal relationships among 1,107 college students. Using an online questionnaire, the study explored how family socioeconomic status, parenting styles, and interpersonal relationships influence mental health literacy. The results showed that family socioeconomic status significantly and positively predicts mental health literacy. Both positive and negative parenting styles were found to partially mediate the relationship between family socioeconomic status and mental health literacy. Additionally, interpersonal relationships partially mediated this relationship. Finally, the study revealed that positive and negative parenting styles acted as sequential mediators between family socioeconomic status and mental health literacy through interpersonal relationships. These findings provide insights into the mechanisms by which family socioeconomic factors shape mental health literacy among college students.